Glaciers Variation at ‘Shocking’ Pace in the Northeastern Margin of Tibetan Plateau from 1957 to 21st Century: A Case Study of Qiyi Glacier - Peihong Shi; Bangshuai Han; Keqin Duan; Liguo Cao; Anan Chen; Yuwei Wu (Atmosphere, 2023)
Accelerating glacier shrinkage is one of the most consequential of global warming. Yet, projections for the region remain ambiguous because of the tremendous spatial heterogeneity, especially in the Qilian Mountains, where glacier melt runoff is a vital water resource for the arid downstream area. To better understand glacier changes in this region, this study took regional representative Qiyi Glacier as an example and applied an enhanced distributed surface mass balance (SMB) model to glimpse the SMB variation and possible impacts on melt runoff under the RCP 4.5 and RCP 8.5 scenarios. Further, we combined a modified volume-scaling method to update the glacier geometry gradually to enhance long-term reliability. When forced with observed daily temperature and precipitation, the reconstructed glacier SMB, from 1957 through 2013, agrees well with the in situ observations. The result indicates an abrupt change for SMB from positive to negative in 1992 and subsequent mass accelerated loss after 2000. The increased summer air temperature and the pattern of large-scale atmospheric circulation shifts might both cause these changes. Using projected climate forcing from as many as 31 coupled GCMs from the CMIP 5 ensemble, the Qiyi Glacier is projected to undergo sustained SMB loss throughout the 21st century for both RCPs. By 2100, the Qiyi Glacier will lose ~25 m water equivalent (w.e.) for RCP 4.5 and ~37 m w.e. for RCP 8.5. Whereas the glacier area will shrink by 43% for RCP 4.5 and 54% for RCP 8.5 relative to 2013 glacier content, corresponding to the volume of the Qiyi Glacier will lose by 54% for RCP 4.5 and by 65% for RCP 8.5, accordingly. Simultaneously, the glacier terminus will experience extreme melts. The terminus elevation of the Qiyi Glacier will retreat from 4310 m a.s.l. in 2013 to 4810 m a.s.l. (RCP 4.5) and 4838 m a.s.l. (RCP 8.5) by the end of 2100, which will exceed the multi-year average ELA (4749 m) from 1957 to 2013. If the warming trends keep and glaciers melt like the Qiyi Glacier with this ‘shocking’ rate, it will raise the possibility of crippling, long-term water shortages for Hexi corridors.